The Routledge handbook of war and society Iraq and Afghanistan - Carlton-Ford, Steven; Ender, Morten G. 1960- (Routledge international handbooks, 2011)
Provides an introduction to sociological and behavioral research on the effects of the wars in Iraq and Afghanistan. Analyzing the effect of the two wars on military personnel and civilians, this handbook is of interest to students of the Iraq and Afghanistan wars, military sociology and psychology, war studies, anthropology, and US politics.